Construct 2 Interactive Multimedia for Temperature and Heat Topic: A Multimedia Development for Senior High School Learning - Maharani, Putri; Asyhari, Ardian (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aimed to develop interactive multimedia using construct 2 on the topic of temperature and heat. The research method used is Research and Development (R and D) which adopted the development of Borg and Gall. Based on the results of the validation from the content experts, the results obtained were 81% in the very good category, and the media experts gave a score of 94% for the very good category, and the results of the teacher’s response obtained a percentage score of 77% in the good category. Then interactive multimedia was tested through two stages, small group trials and field trials. The average results obtained were 83.6% for small group trials, and the results of field trials in three schools were 85%, 84%, and 84%, and the average was 85.7% in the very good category. So, it can be concluded that interactive multimedia is feasible and good for use in learning.